'Medical altruism in mainstream health economics: theoretical and political paradoxes' comments. Issue 2 (2nd April 2016) - O'Boyle, Edward J.; O'Boyle, Meade P.
Abstract: In this article, which was published in the September 2014 issue of the Review, Batifoulier and Da Silva examine the role of medical altruism in health economics. They argue that abandoning homo economicus and the mainstream practice of incorporating patient well-being in the doctor's utility function in order to explain the clinical behavior of doctors and switching from profit maximization to medical altruism both lead to a dead end. We agree but the authors leave us with no way out. We argue instead that the doctor's clinical behavior whether expressed in terms of utility or altruism is not a fit subject for economics. The way out is to restrict economics to health care issues with financial dimensions. In their article, Batifoulier and Da Silva bring their French experience to the table. We bring to the table our American experience with more than 40 years of hands-on care for patients along with the experiences of four other physicians in our extended family. The specialties include intensive care pediatrics, emergency medicine, intensive-care pulmonary medicine, dermatology, and otolaryngology. Our premise in responding to Batifoulier and Da Silva is that apart from payment for services rendered, there probably are no serious differences in the actual practice of medicine in France compared to the United States. And even if there are such differences, they are matters to be taken up by medicine not economics.